Developing an integrated BIM/LCA framework to assess the sustainability of using earthen architecture. Issue 1 (1st September 2022) - Estève, P; Beckett, C; Pedreschi, R; Bosche, F; Morel, J C; Charef, R; Habert, G
Abstract: The construction industry is responsible for one-quarter of the solid waste generated globally, much of which is excavated soil. Repurposing this soil for the use of earthen architecture (EA) will reduce a considerable amount of this waste. However, little research has been conducted on how to assess the use of EA within the architectural, engineering, environmental and economic context, and in comparison with other construction system solutions. This paper presents the development of an integrated building information modelling (BIM) and life cycle assessment (LCA) framework to explore what advantages EA may have, based on the client's needs and the building's requirements. The decision-making conditions and criteria for the use of EA are firstly identified in an extensive literature review supported by interviews with decision-makers. A workflow is secondly proposed to apply a LCA evaluating the decision criteria in a BIM tool at the early-design stages. This method allows for the evaluation and comparison of choice criteria as functional requirements of the building and objectives set by the decision-makers. The flexibility of setting input parameters in this tool increases the visibility of the potential benefits of EA over other construction systems. Along with this approach, upcoming applications on case studies will aim to be replicable by designers, based on their practices and design tools, to support clients in their choice of using EA.